THE CONFORMITY WITH INTEGRATED REPORTING ADOPTED BY INDONESIAN MINING COMPANIES IN THE EARLY STAGES OF NEW REGULATION - Kenny Fernando (Jurnal Penelitian Akuntansi (JPA), 2022)
Sustainability has become a pivotal issue ever since the world’s environment has started declining. The economic aspect no longer stands alone; it must be accompanied by social and environmental aspects. Companies earn profit by ensuring that their operations always add value to the community (including global sustainability development), which eventually affects their stakeholders. This paper highlights an alternative means of communicating what companies have accomplished through integrated reporting (initiated by the International Integrated Reporting Council), which emphasizes value creation for the short, medium, and long term. By assessing such documents, we found that the Indonesian regulation in reporting and the International Integrated Reporting Framework fulfilled 40% and 90%, respectively, of the information needed by stakeholders. Another 22% was accounted for by reconciling both regulatory documents. Surprisingly, we found that seven LQ45 mining companies have exceeded the required information by half in conforming to international regulations.